2007
DOI: 10.1111/j.1600-6143.2006.01687.x
|View full text |Cite
|
Sign up to set email alerts
|

Shipment of Human Islets for Transplantation

Abstract: The use of regional human islet cell processing centers (ICPC) supporting distant clinical islet transplantation programs (CITP) has proven successful in recent clinical trials. Standardization of islet shipping protocols is needed to preserve cell product identity, quantity, quality and sterility, and to meet criteria for transplantation. We evaluated the use of gas-permeable bags for human islet preparation shipment from a single ICPC to two remote CITPs. Product release tests (counts, purity, viability, ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
89
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 43 publications
2
89
0
Order By: Relevance
“…30 The shortage of donors and the exceptional amount of tissue necessary for successful islet transplants limits the procedure's usefulness as a widely-available therapeutic intervention. While stem cells or animal sources may eventually produce unlimited supplies of tissue for transplant, improved understanding of islet biology will allow more rapid adjustments in the current transplant procedure that may improve outcomes since a loss of islets after isolation is commonly observed, 31 and negatively affects transplant outcomes. The results here suggest that the diffusion barrier in large islets leads to core cell death followed by complete loss of the islets.…”
mentioning
confidence: 99%
“…30 The shortage of donors and the exceptional amount of tissue necessary for successful islet transplants limits the procedure's usefulness as a widely-available therapeutic intervention. While stem cells or animal sources may eventually produce unlimited supplies of tissue for transplant, improved understanding of islet biology will allow more rapid adjustments in the current transplant procedure that may improve outcomes since a loss of islets after isolation is commonly observed, 31 and negatively affects transplant outcomes. The results here suggest that the diffusion barrier in large islets leads to core cell death followed by complete loss of the islets.…”
mentioning
confidence: 99%
“…Recently, the advantages of cultured islets before transplantation have been demonstrated over freshly isolated islets (Herring et al, 2004;Ichii et al, 2007). It is known that cellular stress due to pancreas preservation and islet isolation process leads to a loss of islets during the first 24 h after isolation.…”
Section: Preservation Of Islets In Vitromentioning
confidence: 99%
“…Another possible issue with the pre-cultured islets is the possibility of islet fusion during incubation, which may lead to hypoxia and starving of the cells. Those result in central necrosis of fused islet aggregates causing a significant loss of islet potency and viability (Ichii et al, 2007).…”
Section: Preservation Of Islets In Vitromentioning
confidence: 99%
“…We also reported that the clinical outcome in patients who received cultured islets was significantly lower than in patients who received fresh islets, although the number of subjects evaluated was not sufficient to draw definitive conclusions [50] . It is well documented that isolated islets deteriorate rapidly in culture [41,42,50,51] . Since barely half of the processed pancreata meet the criteria for clinical transplantation in most centers, islet loss during culture results in an even lower transplant rate.…”
Section: Islet Culture/preservationmentioning
confidence: 99%